Al-Qur’an Sebagai Media Pembelajaran - Evie Kareviati (STAI Siliwangi Bandung, 2015)
In teaching learning process, teacher has a good role, but media is also very important. Because not all of material can be explained by delivering speech or discussion. And not all students can easily understand the material. Pictures, cards, films usually help teachers in teaching learning process. Media that we used is almost never related to the religion, especially Islam, even though muslim has Qur’an as a holy book. And of course it is a very extraordinary media for teaching and it will make the students smart and religious.